Aboriginal Language and School Outcomes: Investigating the Associations for Young Adults - Anne Guevremont; Dafna Kohen (International Indigenous Policy Journal, 2017)
Being taught an Aboriginal language at school has generally been associated with positive school outcomes for Aboriginal children but not adults. This study attempted to understand this discordance by examining three possible explanations: (a) confounding variables, (b) a cohort effect, and (c) differences in the timing and duration of Aboriginal language instruction. Confounding variables (school attendance on reserve, parental education, and family residential school attendance) and duration of Aboriginal language instruction (six of more grades) were important contributors; whereas the presence of a cohort effect and the timing of Aboriginal language instruction were not found to be significant. Future studies of Aboriginal language instruction should consider family educational experiences, location of schooling, and the duration of Aboriginal language instruction.Being taught an Aboriginal language at school has generally been associated with positive school outcomes for Aboriginal children but not adults. This study attempted to understand this discordance by examining three possible explanations: (a) confounding variables, (b) a cohort effect, and (c) differences in the timing and duration of Aboriginal language instruction. Confounding variables (school attendance on reserve, parental education, and family residential school attendance) and duration of Aboriginal language instruction (six of more grades) were important contributors; whereas the presence of a cohort effect and the timing of Aboriginal language instruction were not found to be significant. Future studies of Aboriginal language instruction should consider family educational experiences, location of schooling, and the duration of Aboriginal language instruction.